(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
The Chittagong-Comilla-Sylhet regions of the Chittagong-Tripura Fold Belt host most of the gas fields in Bangladesh, primarily within the anticlinal structures. The Tertiary Bhuban and Boka Bil formations are the key hydrocarbon-bearing zones where hydrocarbon has been encountered at depths ranging from 1000 to 4000 m in various producing gas fields. The study aims to analyze the hydrocarbon prospects in the shallower stratigraphic successions, particularly the upper part of the Boka Bil Formation in a commercial gas field in Bangladesh where gas is being extracted from depths of 3000–4000 m. Utilizing 3D seismic and wireline log data, we assessed the shallower prospective zones above the conventional producing depth, extending up to 2000 m, which have not yet been explored for hydrocarbon potential in the field. In the study, a classical interpretation approach, precise horizon mapping, and application of various seismic attribute analysis techniques are used to highlight amplitude anomalies indicative of gas accumulation. Results suggest the existence of a new gas-bearing zone at with an estimated resource potential of approximately 23.75 billion cubic feet (BCF). Correlating the new prospective zone with the similar geologic features (channel bounded strata showing higher reflection) observed in deeper producing zone of the field enhances the confidence of our findings. This study may open new prospecting avenues for exploration in the studied field as well as the adjacent fields. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(2), 2024, P 1-16